Overview of the implementation of the reproductive health MISP program: Between policy and field realities - Bariana Widitia Astuti; Julaikah; Dwi Hariyanti (Riset Informasi Kesehatan, 2026)
Background: Disasters have led to the emergence of various diseases and health threats, causing a health crisis, especially for women and girls who are disproportionately affected by disruptions to sexual and reproductive health services among vulnerable populations. Various guidelines and regulations that are available and implemented nationally are expected to reduce morbidity and mortality rates as well as various safety risks that arise, especially those related to reproductive health in health crisis situations. The Indonesian government, through the Ministry of Health, has developed technical guidelines for minimum initial service packages (MISP) since 2014 and implemented them for the first time in 2018. Bantul Regency, particularly the Imogiri sub-district, is an area with a high frequency of disasters and was one of the areas affected by disasters in 2025. The objective of this study is to determine the implementation of minimum initial service packages (MISP) in practice and the suitability of their implementation with available policies, particularly in the Imogiri sub-district of Bantul Regency. Method: This study used a qualitative approach with inductive content analysis. The research subjects involved were elements of the Bantul Health Office, the Health Crisis Center Coordinator at primary health care, the Head of Wukirsari Village, Health Cadres, and beneficiary communities in the Imogiri sub-district. Data collection was carried out using in-depth interviews and semi-structured questions. Results: This study measured and assessed the status and level of program implementation, distribution of facilities and infrastructure (MISP kits), implementation of data collection, documentation, and coordination activities, program education and socialization, as well as challenges during program implementation. Conclusion: The implementation of the minimum initial service package (MISP) for reproductive health in Bantul district is not yet in accordance with the policies that have been established nationally. The main obstacles to the implementation of this program are policies, commitment, and funding at the provincial level.